2008
DOI: 10.1136/adc.2007.134692
|View full text |Cite
|
Sign up to set email alerts
|

Developmental coordination disorder in "apparently normal" schoolchildren born extremely preterm

Abstract: Apparently normal high-risk infants are at risk of motor dysfunction into their school years. Most of these could be identified at age 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
134
3
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(162 citation statements)
references
References 37 publications
9
134
3
16
Order By: Relevance
“…Pregnancy-induced hypertension was defined as the development of new arterial hypertension (blood pressure over 140/90 mmHg) during pregnancy, after 20 weeks gestation and without proteinuria. Given the association of PROM with poor motor outcome [8][9][10], we examined the role of chorioamnionitis as measured by placental histopathology, a more sensitive measure of intrauterine infection [25]. To measure early illness severity, we used SNAP-II during the first 24 hours of life; SNAP-II quantifies six physiological variables (blood pressure, temperature, PO 2 /fraction of inspired oxygen, serum pH, seizures, and urine output), with higher scores reflecting more disturbances in neonatal physiology [14].…”
Section: Clinical Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy-induced hypertension was defined as the development of new arterial hypertension (blood pressure over 140/90 mmHg) during pregnancy, after 20 weeks gestation and without proteinuria. Given the association of PROM with poor motor outcome [8][9][10], we examined the role of chorioamnionitis as measured by placental histopathology, a more sensitive measure of intrauterine infection [25]. To measure early illness severity, we used SNAP-II during the first 24 hours of life; SNAP-II quantifies six physiological variables (blood pressure, temperature, PO 2 /fraction of inspired oxygen, serum pH, seizures, and urine output), with higher scores reflecting more disturbances in neonatal physiology [14].…”
Section: Clinical Data Collectionmentioning
confidence: 99%
“…Our aim was to explore in a prospective cohort of premature newborns serially studied with diffusion tensor imaging, the associations of established risk factors for motor impairment with development of the major motor pathway measured with diffusion tensor tractography. These risk factors include antenatal exposures, such as pregnancy-induced hypertension [6], gestational diabetes [7], and intrauterine inflammation [8][9][10], as well as male sex [11][12][13]. Putative perinatal and post-natal risk factors include early illness severity as measured by the Score of Neonatal Acute Physiology-Version II (SNAP-II) [14,15], infection [9,16,17], necrotizing enterocolitis [16,17], patent ductus arteriosus [18], chronic lung disease [18][19][20][21], and neonatal procedural pain [22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of school-age survivors have highlighted a significant excess of mild neuromotor dysfunction (Davis, Ford, Anderson, & Doyle, 2007;Fawke, 2007;Goyen & Lui, 2009;Wocadlo & Rieger, 2008), poor visuospatial processing (Marlow, Hennessy, Bracewell, & Wolke, 2007;Taylor, Burant, Holding, Klein, & Hack, 2002;Taylor, Klein, Minich, et al, 2000), and impairments in attention and executive functions (Aarnoudse-Moens, Smidts, Oosterlan, Duivenvoorden, & Weisglas-Kuperus, 2009; Anderson & Doyle, 2004;B. Bohm, Smedler, & Forssberg, 2004;Marlow et al, 2007;Mulder, Pitchford, Hagger, & Marlow, 2009).…”
mentioning
confidence: 99%
“…The prevalence of DCD in children born extremely premature (<29 weeks) or with extremely low birth weight (<1000 g) has been reported to be high, which was around 42% in one study. 29 A recent meta-analysis of studies in school-aged children with very low birth weight (VLBW)/very preterm reported an odds ratio (OR) of up to 8.66. 30 In our study, 6.5% and 10.8% of children had a history of prematurity or low birth weight, respectively, but none was born very preterm or with VLBW.…”
Section: Discussionmentioning
confidence: 99%